The Telehealth Effectiveness in Home Care Services: A Systematic Review - Nurtarina Heratanti; Angelina Pinkan Rambi; Islam Syarifurrahman (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Telehealth is a technology-based system that facilitates remote health management. This study aimed to examine the telehealth’s effectiveness in home care services. Methods: The Systematic literature was carried out on the last five years of research from 5 indexed electronic databases. This study used PICOS framework as a guideline in finding articles. The RCT examined the telehealth’s effect in home care services. The methodological quality used JBI critical appraisal checklist. The study’s major findings showed that Telehealth in home care services is quite effective both in providing services, increasing the competence of nurses, and making it easier for patients to do it from home. Telehealth interventions are effective and feasible for use in home care patients who have chronic disease, and provides satisfaction in providing services to both patients and nurses